Is the depth of cone related to the endocervical glandular involvement in patients who underwent loop electrosurgical excision procedure or cold knife conization? - Akış, Serkan; Purut, Yunus Emre; Keleş, Erhan; Api, Murat; Kabaca Kocakuşak, Canan; Giray, Burcu; Ceylan, Yasemin; Güray Uzun, Mine (BMJ Publishing Group, 2019)
[Abstract Not Available]
Keywords: Cold Knife Conization; Electrosurgical Excision; Endocervical Glandular